Is platform work migrant work? The economic and social conditions behind migrant (over-)representation in the platform economy across Europe. - Piasna, Agnieszka; Zwysen, Wouter (International Labour Review, 2026)
This article investigates the over-representation of migrant workers in the platform economy across 14 European Union Member States, using representative survey data from the 2021 European Trade Union Institute Internet and Platform Work Survey (IPWS) and complementary EU Labour Force Survey statistics. It finds that migrants are about 20% more likely than non-migrants to engage in platform work, particularly in location-based transport and delivery services, though nearly half of this difference is explained by migrants’ socio-demographic characteristics such as age, education, and employment status. The study highlights that migrants who are more vulnerable—especially those without traditional employment, with higher education facing recognition barriers, or belonging to groups experiencing greater labour market penalties—are more likely to participate in platform work, which often serves as an alternative due to limited access to decent jobs in the traditional economy. The findings suggest that platform work’s relatively lower entry barriers compared to conventional employment attract migrants but may also contribute to their long-term labour market disadvantage and social exclusion. The article emphasizes the need for integrated policy approaches addressing labour standards both in traditional and platform economies to protect vulnerable workers, including migrants.